The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1159/000078747
|View full text |Cite
|
Sign up to set email alerts
|

IGFs, IGFBPs, IGF-Binding Sites and Biochemical Markers of Bone Metabolism during Differentiation in Human Pulp Fibroblasts

Abstract: Objective: To investigate the role of the insulin-like growth factors (IGF) system during the differentiation of human pulp-derived fibroblasts (HPF). Methods: Primary HPF were cultured for 24 days in DMEM medium with IGF-I or IGF-II (50 ng/ml each). Cell growth and morphology, alkaline phosphatase (ALP) activity, the concentration of free deoxypyridinoline (DPD), IGF-I, -II, IGFBP-2 and -3 were studied. The number of 125I-IGF-I binding sites was estimated by Scatchard analysis. Results: Light-micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
2
7
1
Order By: Relevance
“…We have recently confirmed that IGF2 peptide is present at 10-fold higher concentrations in differentiated DPCs compared to cells grown under basal conditions (Al-Khafaji et al submitted for publication). We believe our data represent the first demonstration of increased IGF2 expression under mineralization conditions in DPCs and confirm previous findings that IGF2 is the main IGF species expressed in dental pulp (Reichenmiller et al, 2004 ). IGF2 may be sequestered in the matrix during dentin formation and released during demineralization of dentin.…”
Section: Discussionsupporting
confidence: 92%
“…We have recently confirmed that IGF2 peptide is present at 10-fold higher concentrations in differentiated DPCs compared to cells grown under basal conditions (Al-Khafaji et al submitted for publication). We believe our data represent the first demonstration of increased IGF2 expression under mineralization conditions in DPCs and confirm previous findings that IGF2 is the main IGF species expressed in dental pulp (Reichenmiller et al, 2004 ). IGF2 may be sequestered in the matrix during dentin formation and released during demineralization of dentin.…”
Section: Discussionsupporting
confidence: 92%
“…Conversley IGF-2 and IGF-1R were expressed at moderate to high levels in our experiments confirming previous reports (Caviedes-Bucheli et al, 2004, Shi et al, 2001). Both IGF-1 and IGF-2 (acting via the IGF-1R) can induce ALP activity in canine dental pulp cells (Onishi et al, 1999) and IGF-2 secretion was reported during matrix mineralisation of human dental pulp derived fibroblasts (Reichenmiller et al, 2004). IGF axis components are present in other dental structures with IGF-1 and -2 along with all six IGFBPs present in the ECM of the periodontal ligament and IGF-1R present on the surface of periodontal ligament derived fibroblasts (Gotz et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, DPSC show higher self‐renewal ability, immunomodulatory capacity, and proliferation in vitro than BM‐MSC, and they differentiate preferentially to osteoblasts rather than to adipocytes [6, 15]. These cells, like BM‐MSC, are able to secrete vascular endothelial growth factor (VEGF) [16, 18], insulin‐like growth factor‐1 (IGF‐1) and ‐2 (IGF‐2) [13, 19, 20], stem cell factor (SCF), and granulocyte‐colony stimulation factor [21, 22], all of which can exert proangiogenic, antiapoptotic, and cardioprotective actions [3, 23, 24]. Thus, the aim of this study was to determine whether DPSC could be useful for cardiac repair, in a rat model of MI.…”
Section: Introductionmentioning
confidence: 99%